Three-dimensional echocardiography as a predictor of positive response to cardiac resynchronization therapy - Mohamed Elsayed Abdelfattah, Reda Biomy Bastawisy; Hany Mahmoud; Abdel Shakour; Wael Anwar Haseeb (Journal of the Pakistan Medical Association, 2023)
N/A